Case report: Biliobronchial fistula after biliary tract stenosis - Batalin Júnior, Luís Maurício; Zandoná, Mariana Conceição e Silva Seleme; Vargas, Thomaz Almeida; Oliveira, Julio Cesar de; Chiappetto, Juliana Rocha Souza; Oliveira, Cassio Vieira; Romeiro, Fernando Gomes; Tanni, Suzana Erico (Frontiers in Medicine, 2022)
Biliobronchial fistula (BBF) is a rare abnormality resulting from congenital or acquired communication between the bile ducts and the bronchial tree. Patients often suffer from chronic cough, dyspnea, and bilioptysis, a pathognomonic symptom of this condition. Conservative methods such as less-invasive procedures are gradually consolidating. Nonetheless, surgery remains the primary treatment, especially for more complex cases. We report a 44-year-old woman who presented with chronic cough, no verified periods of fever, cyclic jaundice, and episodes of yellowish sputum. She had undergone cholecystectomy in 2018 and was hospitalized several times after the procedure for treatment of pneumonia. All consequent investigations of mycobacteriosis were negative. When referred to our hospital, she had cyclic jaundice and presence of the right lower lobe with parenchymal consolidation. Suspicion of bilioptysis motivated the research of a biliobronchial fistula. Colangio magnetic resonance imaging (MRI) confirmed the stenosis of the biliary tract and the fistulous path, and the sputum analysis indicated high bilirubin levels. Initial therapy performed was an external biliary bypass with further biliary tract reconstruction. Although BBF is a rare condition when bilioptysis is suspected, diagnostic investigation should to be initiated. Our case study proposes two criteria for diagnosis: an imaging exam demonstrating the fistulous path and the confirmation of bilirubin in the sputum or bronchoalveolar lavage (BAL). When the diagnostic is performed, surgical correction should be performed.